2015
DOI: 10.1007/s40011-015-0591-0
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Cultivation of Ferula jaeschkeana Vatke: A Species with Deep Complex Morphophysiological Dormancy

Abstract: Ferula jaeschkeana Vatke, an important medicinal plant of the Himalayan region, being threatened needs immediate conservation strategies. Keeping this in view studies on the germination of seeds and sprouting of vegetative propagules has been undertaken for the first time. At the time of dispersal, F. jaeschkeana seeds are dormant and have under-developed embryos. The aims of the present work were to determine the requirements for germination and overcoming dormancy and to characterize the type of seed dormanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, we believe that these studies have not shown a complete picture of dormancy in F. ovina. The existence of morphophysiological dormancy (MPD) is very frequent in the Apiaceae (Baskin et al, 1992(Baskin et al, , 1995(Baskin et al, , 2000Phartyal et al, 2009;Vandelook et al, 2008Vandelook et al, , 2009Scholten et al, 2009;Yaqoob and Nawchoo, 2015). Also in the case of closely related species of F. gummosa and F. asafoetida, there are reports of MPD (Otroshi et al, 2009;Rouhi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, we believe that these studies have not shown a complete picture of dormancy in F. ovina. The existence of morphophysiological dormancy (MPD) is very frequent in the Apiaceae (Baskin et al, 1992(Baskin et al, , 1995(Baskin et al, , 2000Phartyal et al, 2009;Vandelook et al, 2008Vandelook et al, , 2009Scholten et al, 2009;Yaqoob and Nawchoo, 2015). Also in the case of closely related species of F. gummosa and F. asafoetida, there are reports of MPD (Otroshi et al, 2009;Rouhi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ferula jaeschkeana Vatke is mostly found in the sloppy regions of Kashmir Himalaya and is used in folk medicine for curing various ailments like chest pain, gastric problems, treatment of tumors, chronic wounds and ulcers [12][13][14]. So far no systematic research on comparative studies has been reported on the presence of phytochemicals in Ferula jaeschkeana.…”
Section: Introductionmentioning
confidence: 99%
“…Germination cues for F. assa-foetida and F. gummosa were complex, with dormancy mechanisms present to restrict germination until cold stratification or other requirements are fulfilled (Nadjafi et al 2006;Amooaghaie, 2009;Nowruzian et al 2016;Fasih and Tavakkol Afshari, 2018). The existence of morphophysiological dormancy (MPD) is very frequent in the Apiaceae (Baskin et al 1992(Baskin et al , 1995(Baskin et al , 2000Phartyal et al 2009;Vandelook et al 2008Vandelook et al , 2009Scholten et al 2009;Yaqoob and Nawchoo 2015;Fasih and Tavakkol Afshari 2018). Cold stratification temperature used in this experiment (4°C) provides an adequate moist chilling treatment.…”
Section: Discussionmentioning
confidence: 99%